CEREBRAL SINUS VENOUS THROMBOSIS PADA PENDERITA SYSTEMIC LUPUS ERYTHEMATOSUS - Destika Fahrina,* Mohammad Arief Rachman Kemal,** Adiel Amaris Syah,** Melita,** Lyna Soertidewi** (NEURONA, 2019)
SINUS VENOUS THROMBOSIS CSVT MAY SOMETIMES BE ASSOCIATED WITH AUTOIMMUNE DISORDER LIKE SYSTEMIC LUPUS ERYTHEMATOSUS SLE IT IS CHARACTERIZED BY DURAL VENOUS THROMBOSIS WHICH CAN CAUSE VARIETY OF SYMPTOMS INCLUDING HEADACHE CONVULSION MOTOR WEAKNESS AND DECREASED LEVEL OF CONSCIOUSNESS THROMBOSIS OFTEN OCCURS IN THE LOWER EXTREMITIES IN POSTPARTUM WOMEN DUE TO PROLONGED BED REST AND CAESAREAN SECTION